A Novel PVT Model Incorporating Mass Transfer Rate for Subsurface Data Determination - Review - Hon , Vai Yee (2008)
In field development and reservoir surveillance planning, there is an absolute need to obtain reliable values for reservoir pressures, productivity indexes and other values on a continuous basis so that planning can be done reliably and production / recovery can be optimized. However, continuous data acquisition is often where we stumbled due to a combination of economic, operational/logistical constraints. An alternative is to derive these key parameters from surface data using dynamic well modeling techniques. Subsurface data acquisition will be replaced by surface data acquisition, reducing the number of well interventions and data acquisition costs. The major assumption in current PVT correlations in dynamic well modeling application is instantaneous transformation of one phase (gas) into another phase (oil). During shut-in, this assumption leads to inaccurate modeling of the gas/liquid distribution in the well and hence, an incorrect prediction of interphase level, in-situ density and pressure distribution in the well. The objectives of this research is to improve the current dynamic well modeling technique by incorporating the mass transfer rate model into current PVT model for a reliable well shut-in status description. This is a relatively new and unexplored technical method, which increases the understanding of well behavior. This novel PVT model is able to determine an accurate volume of each fluid phase at any node in the wellbore by incorporating the fluid segregation, mass transfer rate and fluid ingress in the reservoir during shut-in. This better description of wellbore dynamic behavior improves the accuracy of dynamic well modeling ensuring a reliable downhole data determination. This paper presents a status update in well performance modeling and the proposed scheme in developing the novel PVT model. A number of engineering conceptions were reviewed and all the elements that become the foundation of the well bore transient mechanics were discussed.